Protective Factors for the Development of Psycho-pathological Symptoms in Young Victims of Community Violence - Gurrola-Peña, Gloria Margarita (2018)
The objective of the present investigation was to identify the role of life purpose, noetic goals and resilience in the mental health of young victims of community violence. 1,500 students from four universities in northern and central Mexico participated in the study, 988 were women and 512 men, with an average age of 20.8 years. The results indicate high rates of direct and indirect victimization and high psychological distress without development of psycho-pathological symptoms. Linear regression by stepwise indicated that the three variables studied serve as protective elements for the mental health of young victims of community violence.